Meningeal blood–brain barrier disruption in acute traumatic brain injury. Issue 2 (9th September 2020) - Turtzo, Lisa Christine; Jikaria, Neekita; Cota, Martin R; Williford, Joshua P; Uche, Victoria; Davis, Tara; MacLaren, Judy; Moses, Anita D; Parikh, Gunjan; Castro, Marcelo A; Pham, Dzung L; Butman, John A; et al.
Abstract: The meninges serve as a functional barrier surrounding the brain, critical to the immune response, and can be compromised following head trauma. Meningeal enhancement can be detected on contrast-enhanced MRI in patients presenting with acute traumatic brain injury, even when head CT is negative. Following head trauma, gadolinium-based contrast appears to extravasate from the vasculature, enhancing the dura within minutes, and later permeates the subarachnoid space. The aims of this study were to characterize the initial kinetics of the uptake of contrast agent after injury and the delayed redistribution of contrast enhancement in the subarachnoid space in hyperacute patients. Neuroimaging was obtained prospectively in two large ongoing observational studies of patients aged 18 years or older presenting to the emergency department with suspected acute head injury. Dynamic contrast-enhanced MRI studies in a cohort of consecutively enrolling patients with mild traumatic brain injury ( n = 36) determined that the kinetic half-life of dural-related meningeal enhancement was 1.3 ± 0.6 min (95% enhancement within 6 min). The extravasation of contrast into the subarachnoid space was investigated in a cohort of CT negative mild traumatic brain injury patients initially imaged within 6 h of injury (hyperacute) who subsequently underwent a delayed MRI, with no additional contrast administration, several hours after the initial MRI. Of the 32 patients with delayed post-contrast imaging, 18 (56%) had conspicuous expansion of the contrast enhancement into the subarachnoid space, predominantly along the falx and superior sagittal sinus. Patients negative for traumatic meningeal enhancement on initial hyperacute MRI continued to have no evidence of meningeal enhancement on the delayed MRI. These studies demonstrate that (i) the initial enhancement of the traumatically injured meninges occurs within minutes of contrast injection, suggesting highly permeable meningeal vasculature, and that (ii) contrast in the meninges redistributes within the subarachnoid space over the period of hours, suggesting a compromise in the blood–brain and/or blood-cerebrospinal barriers. Data from the parent study indicate that up to one in two patients with mild traumatic brain injury have traumatic brain injury on acute (<48 h) MRI, with a higher prevalence seen in patients with moderate or severe traumatic brain injury. The current study's findings of traumatic meningeal enhancement and the subsequent delayed extravasation of contrast into the subarachnoid spaces indicate that a substantial percentage of patients with even mild traumatic brain injury may have a transient disruption in barriers separating the vasculature from the brain. Abstract : After mild traumatic brain injury, traumatic meningeal enhancement and extravasation of contrast into subarachnoid space can be detected within hours of injury. The presence of these novel neuroimaging markers suggests that blood-meningeal barriers can be compromised in the acute phase, even in patients with no other findings of intracranial injury. Graphical Abstract: